Determination of Public Awareness on Water Stress, Water Scarcity and Water Saving: Akdeniz University Case Study - Aslı Gezer; Ayça Erdem (Doğal Afetler ve Çevre Dergisi)
As the population of the world increases, the water resources rapidly decrease. It is predicted that the population having water stress today will have water shortage in the future. Turkey is among the countries having lack of water and is in danger of becoming a water poor country. Due to the increasing water demand around the world, various measures are being taken starting from the local scale. In addition to these measures, the levels of awareness and perception of public on environmental issues are evaluated. Surveys applied from regional to national scale provide data and guidance to the institution, municipality and ministries that produce works and policies related to water management. In this study, the survey results on the awareness of 300 participants, who work, study and reside within Akdeniz University campus, on "water scarcity, water stress and water saving" are given. The responses to the survey were analyzed with SPSS Statistics Base V23 licensed program. The responses were evaluated according to the demographic information (age, gender and monthly income level) using chi-square analysis. According to the survey results; (i) regardless of gender and age, the vast majority of participants have a similar tendency to use water, (ii) women are more susceptible to water stress, water scarcity and water saving than men, and (iii) as the income level increases, the sensitivity of water use also increases.